Pengaruh Soft Control Dan hard Control Terhadap Hasil Temuan Auditor Internal Di Perusahaan Daerah Air Minum Se Provinsi Banten - Husni, Mohamad (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2019)
This research aims to test the impact of  integrity and ethical values, commitment to competence, Tone at the Top, work culture, organizational structure, Sop and supervision of the findings of the Internal Auditor Regional Water Company (PDAM) in the province of Banten. The samples in this study using purposive sampling method. Data were collected using a questionnaire survey techniques. The target respondents of this study were 100 respondents, but the data is data that can be processed is 83 respondents. To test the quality of the data from the instrument used to do with the validity and test ralibilitas. Test the classical assumption of normality test, multicollinearity, homogeneity test and test heterkodastisitas is intended as a requirement to perform multiple linear regression test.            The results of multiple regression analysis showed that the variation of the variable findings of the internal auditor can be explained by the variable of integrity and ethical values, commitment to competence, tone at the top, work culture, organizational structure, soup and supervision 52.9 percent, t test showed that the variables Integrity and ethical values, commitment to competence, Sop and Supervision affect the findings of the internal auditor, while variable Tone at the Top, Culture Work and Organizational Structure there are no influence against the findings of the internal auditor.            The results of research shows that Integrity and Ethics Values, Commitment Competence, SOP and Oversight had a positive influence on the Findings of the Internal Auditor. The test results provide a synthesis hypothesis that the better Integrita and ValuesEthics, Commitment Competence, SOP, and the stronger the less oversight findings of internal auditors found (fewers error)